VILLAGE FUND MANAGEMENT ACCOUNTABILITY IN ORAHILI TUMORI VILLAGE - Parta Junius Zebua; Yearning Harefa; Sophia Molinda Kakisina (Jurnal Ekonomi, 2022)
This study aims to find out about village fund management centered on administration and reporting in Orahili Tumori Village for the 2018 fiscal year. Orahili Tumori Village Finance has implemented 5 principles recommended by the United Nations Development Program (UNDP) namely transparency, control, obligation, responsiveness and responsibility for managing village funds. However, village heads have not fully implemented these 5 principles and must improve their performance in reporting the APBDes Implementation Report in a timely manner. The research method used is qualitative with a descriptive type. The data is done by observation, interviews and documentation. Analysisresult show that Bendungan Village Finance Department has implemented five principles recommended by the United Nations Development Program (UNDP) to distribute state funds: transparency, control, obligation, responsiveness, and responsibility. Therefore, the village management of the Dam Village fund has been legalized. However, the Dam Village Head's principles of control, obligations (obligations), and responsibilities have yet to be implemented and require further work to continue.